Liminal Personhood and Continuity of Moral Identity in Clinical Care - Harvey Max Chochinov; Marianne Sofronas; Joseph J. Fins (Journal of Palliative Medicine, 2026)
Capacity-based frameworks of personhood risk marginalizing individuals whose agency, cognition, or consciousness are diminished by illness, brain injury, or proximity to death. This article introduces the concept of liminal personhood , which describes the persistence of moral and relational identity even as conventional markers of personhood fade. Drawing on ethical, philosophical, and neuroethical scholarship, the paper argues that failing to recognize enduring personhood can fracture patient identity and erode clinician and caregiver moral integrity. Recognition of liminal personhood has clear clinical utility: It guides dignity-conserving care, supports relational engagement, and sustains clinicians’ ethical coherence amid profound vulnerability, thus offering a practical framework for humane care at the edges of consciousness and decisional capacity.